PEMANFAATAN TEPUNG PISANG KEPOK DAN TEPUNG TEMPE DALAM PEMBUATAN KUKIS - Muhammad Suhadah Malau; Yusmarini; Vonny Setiaries Johan (Fakultas Pertanian Universitas Riau, 2022)
Cookies are a type of snack that tastes sweet, has a crunchy texture, made from flour with other additives such as eggs, margarine, powdered sugar, and powdered milk. The purposes of this research were to obtain the best ratio between kepok banana flour and tempe flour for making cookies with appropriate nutritional content SNI 01-2973-2011. The study was conducted using a completely randomized design (CRD) with five treatments and three replications. The treatment in this research was the difference of the ratio between kepok banana flour and tempe flour, namely PTI (100:0), PT2 (95:5), PT3 (90:10), PT4 (85:15) and PT5 (80:20). Data were analyzed using analysis of variance (ANOVA) and then continued with Duncan’s new multiple range test (DNMRT) at 5% level. The result showed that the ratio of kepok banana flour and tempe flour significantly affected moisture, ash, protein, fat, carbohydrate, as well descriptive and hedonic sensory overall tests. The ratio of kepok banana flour and tempe flour (85:15) was chosen as the best treatment which had 7.1% protein, 4.5% moisture, 2.6% ash, 7.7% fat, 78.8% carbohydrate, with a description of brown, slightly flavored banana kepok, crumbly texture, slightly tempe taste, and overall hedonic assessment were liked by panelists.